Lossy source coding algorithm using lossless multi-terminal source codes - Muramatsu, J.; Miyake, S. (2008 International Symposium on Information Theory and its Applications, 2008)
A lossy source coding algorithm is presented that employs lossless multi-terminal source codes. By using nearly optimal lossless multi-terminal source codes, the proposed algorithm achieves the rate-distortion limit. The construction of lossless multi-terminal source codes, which are needed for the lossy source coding algorithm, can be realized by using sparse matrices, known as Low Density Parity Check (LDPC) matrices, or Turbo codes, and practically efficient decoding algorithms such as the Belief Propagation (BP) algorithm and the Linear Codes Linear Program (LCLP) algorithm.